Midkine-a Regulates the Formation of a Fibrotic Scar During Zebrafish Heart Regeneration - Grivas, Dimitrios; González-Rajal, Álvaro; de la Pompa, José Luis (Frontiers in Cell and Developmental Biology, 2021)
Unlike the hearts of mammals, the adult zebrafish heart regenerates after injury. Heart cryoinjury in zebrafish triggers the formation of a fibrotic scar that gradually degrades, leading to regeneration. Midkine-a (Mdka) is a multifunctional cytokine that is activated after cardiac injury. Here, we investigated the role of mdka in zebrafish heart regeneration. We show that mdka expression was induced at 1-day post cryoinjury (dpci) throughout the epicardial layer, whereas by 7 dpci expression had become restricted to the epicardial cells covering the injured area. To study the role of mdka in heart regeneration, we generated mdka-knock out (KO) zebrafish strains. Analysis of injured hearts showed that loss of mdka decreased endothelial cell proliferation and resulted in an arrest in heart regeneration characterized by retention of a collagenous scar. Transcriptional analysis revealed increases in collagen transcription and intense TGFβ signalling activity. These results reveal a critical role for mdka in fibrosis regulation during heart regeneration.